Servizi di monitoraggio tecnologicamente sperimentati - Monteleone, Antonio; Dore, Nicole; Benenati, Luca; Bernardi, Lorenzo (Archeomatica, 2018)
ArTeK starts from the experience gained in previous projects that allowed NAIS to develop procedures, develop prototypes of satellite data processing chains and to identify, more and more, the specific needs of end users. The growing development of satellite technologies has in fact allowed to realize, in the last few years, projects focusing on experimentation in the field of innovative services to support the safeguarding of cultural heritage.